Implementasi Nilai-Nilai Pendidikan Agama Islam di Madrasah Tsanawiyah Adzkia Kertaharja Ciamis - Darifah, Udung Hari (Bestari | Jurnal Studi Pendidikan Islam, 2021)
This study aims to elaborate on the implementation of Islamic education values ​​in Madrasah Tsanawiyah Adzkia Kertaharja, Ciamis Regency. The research method used is the method of Qualitative Research (Qualitative Research). Qualitative research is methods to explore and understand the meaning that some individuals or groups of people ascribe to social or humanitarian problems. The implementation of Islamic religious education values ​​is based on (1) aqidah (2) morals (3) respect for reason (4) humanity (5) balance (6) mercy for all nature (rahmatan lil'alamin). Obstacles in the implementation of Islamic religious education values ​​are religious education materials that only focus on enriching knowledge (cognitive) and minimal in forming attitudes (affective) and habituation (psychomotor); lack of participation of teachers of other subjects in motivating students to practice the values ​​of religious education in everyday life; lack of teacher resources in developing more varied approaches and methods; the lack of various training and development facilities, as well as the low participation of parents.